P198 tDCS stimulation of the left inferior frontal gyrus in a connected speech task with fluent speakers. Issue 3 (March 2017) - Bashir, N.; Howell, P.
Abstract : Question: Brocas area (left inferior frontal gyrus; LIFG) has a crucial role in the production of fluent speech, being involved in the planning and coordination of speech processes. Brain stimulation via tDCS modulates accuracy and vocal reaction times in speech tasks employing healthy and impaired individuals. All/most previous studies have been limited as they use single words as stimuli, which is atypical of fluent speech which entails strings of words. The current study examined whether applying tDCS to the LIFG affected participants' ability to articulate tongue twister sentences that are demanding forms of connected speech. Methods: Three groups with eight healthy individuals per group (mean age: 20.17; SD: 1.49) took part. Participants repeated a list of 38 English tongue twisters as quickly and as accurately as possible during three different stimulation conditions: (1) anodal tDCS (20 minutes, 2 mA) over the left frontal region centred on Broca's area; (2) cathodal tDCS delivered over the same region; and (3) sham stimulation. The tongue twisters were repeated on three occasions: an hour before, during and one hour after the end of stimulation. Vocal reaction times, from stimulus offset to response offset, were measured manually from oscillograms in all three stimulation conditions. Results: Anodal stimulation led to significantly quicker vocal reaction times during stimulation compared to sham stimulation at both participant and item levels. Furthermore, vocal reaction times in the post stimulation anodal condition were quicker than sham, at trend levels for participant, and item, analysis. The difference in vocal reaction times between anodal and cathodal stimulation approached significance during stimulation and was significant post stimulation at the item level. Conclusions: The results support and confirm that left frontal regions, particularly Broca's area, are involved in fluent production of speech and show that tDCS modulates speech timing. Since tDCS is a valid means of modulating and investigating fluent connected speech control, it provides a foundation for future work to explore the use of this procedure in articulatory disorders such as stuttering.